Promosi Kesehatan Gigi dan Mulut pada Remaja - Erni Susanty Tahir; Puput Mulyono (Institut Teknologi dan Bisnis Semarang, 2025)
The results of the Basic Health Research (2018) stated that the Indonesian population who have dental and oral problems aged 10-18 years are 61.9% and those aged >18 years are 54.2%. In Central Java Province, there are 56.7% of the population who experience dental and oral problems. Dental problems that often occur in Indonesia are cavities, missing or extracted teeth, filled teeth, and loose teeth. The age group of 10-18 years who experience cavities is 48.5%, missing or extracted teeth is 29%, filled teeth is 4.2%, and loose teeth is 15.9%, and those aged >18 years who experience cavities is 38.6%, missing or extracted teeth is 30.6%, filled teeth is 3.1%, and loose teeth is 15.5%. The results of a survey conducted on 22 teenagers living in Gentan Village on November 10, 2024 obtained data on the condition of dental and oral health and hygiene with an average OHI-S value of 4.9 with criteria (bad) with (DI = 2.4, CI = 2.3) this figure is very high because for good criteria it is 0-1.2 and the DMF-T figure is 1.2 with criteria (low). The implementation method is OHI-S examination, filling out questionnaires, oral gymnastics, prokesgisia gymnastics and counseling. Community service is carried out through interviews and training.